Perancangan Interior Bike Center di Surabaya - Yusita Kusumarini, Dionisius Alfred Widhiaono (Intra, 2014)
âInterior Designing Bike Center in Surabayaâ is an idea to built and provide facilities for people who love sports, specifically cycling, in Surabaya. Cycling is very popular in Surabaya nowadays.The most like are fixed gear bike and road bike.The designer covers the bike lovers with facilities such as a cafÃ©, mini-velodrome track, indoor training or gym, clinic, bike store, workshop, offices, and many other facilities. Linear Design Method is used by designer, and produce visualization design space and a 1:50 scale prototype. Designer presenting mini-velodrome and many other facilities that peoples can enjoy with their community, the design itself is especially for communal activities, so every spaces are designed fot community, not individual.